Oncogenic Function and Early Detection Potential of miRNA-10b in Oral Cancer as Identified by microRNA Profiling - Lu, Ya-Ching; Chen, Yin-Ju; Wang, Hung-Ming; Tsai, Chi-Ying; Chen, Wen-Ho; Huang, Yu-Chen; Fan, Kang-Hsing; Tsai, Chi-Neu; Huang, Shiang-Fu; Kang, Chung-Jan; Chang, Joseph Tung-Chieh; Cheng, Ann-Joy (Cancer prevention research (Philadelphia, Pa.), 2012)
The miRNA participates in a variety of biologic processes, and dysregulation of miRNA is associated with malignant transformation. In this study, we determined specific profile of miRNA associated with oral cancer by using miRNA array screening method. There were 23 miRNAs found with considerably differential expressions between six oral cancer cell lines and five lines of normal oral keratinocytes, in which, 10 miRNAs showed the highest significant difference after independent examination by reverse transcription quantitative PCR. Eight molecules were upregulated, miR-10b, miR-196a, miR-196b, miR-582-5p, miR-15b, miR-301, miR-148b, and miR-128a, and two molecules, miR-503 and miR-31, were downregulated. The most upregulated miR-10b was further examined, and its functions were characterized in two oral cancer cell lines. The miR-10b actively promotes cell migration (2.6- to 3.6-fold) and invasion (1.7- to 1.9-fold) but has minimal effect on cell growth or chemo-/radiosensitivity. Furthermore, miR-10b was considerably elevated in the plasma of xenografted tumor mice (20-fold). This upregulation of miR-10b in plasma was further shown in the patients with oral cancer [P < 0.0001, area under curve (AUC) = 0.932] and precancer lesions (P < 0.0001, AUC = 0.967), suggesting that miR-10b possesses a high potential to discriminate the normal subjects. In conclusion, we have identified at least 10 miRNAs significantly associated with oral cancer, including the most elevated miR-10b. The miR-10b actively participates in cancer formation by promoting cell migration and invasion. Our study using clinical samples suggests that plasma miR-10b has high potential as an early detection marker for oral cancer. Cancer Prev Res; 5(4); 665–74. ©2012 AACR.